2014
DOI: 10.2147/nss.s34846
|View full text |Cite
|
Sign up to set email alerts
|

Sleep–wake disturbances in cancer patients: narrative review of literature focusing on improving quality of life outcomes

Abstract: PurposeEvidence suggests a high prevalence of sleep–wake disturbances in patients with cancer, occurring at diagnosis, during treatment, and continuing to survivorship. Yet associations between sleep–wake disturbances and the impact on quality of life outcomes is less clear. The purpose of this narrative review of the literature is to evaluate sleep–wake disturbances in patients with cancer, to describe the influence of poor sleep on quality of life as an outcome, and to evaluate the evidence to recommend futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
(53 reference statements)
2
30
1
Order By: Relevance
“…Other studies that have used the PGI in cancer samples also found this wide range of areas [9,19]. Our findings are concordant with the literature on the importance of fatigue, sleep, and pain to QOL, as the most recent systematic reviews endorsed their importance [48][49][50][51][52][53].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies that have used the PGI in cancer samples also found this wide range of areas [9,19]. Our findings are concordant with the literature on the importance of fatigue, sleep, and pain to QOL, as the most recent systematic reviews endorsed their importance [48][49][50][51][52][53].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, sleep disturbance in cancer patients have also independently been shown to negatively impact QOL [29]. In our cohort, we did not see an association with increasing sleep disturbance across EBRT treatment weeks.…”
Section: Discussioncontrasting
confidence: 66%
“…However, they generally remained underdiagnosed and poorly treated [170][171][172][173]. In a cross-sectional survey study on nearly 1,000 cancer patients to examine the prevalence of sleep problems, sleep disturbance was most prevalent among the lung and breast cancer patients.…”
Section: Clinical Application Of Melatonin In Cancermentioning
confidence: 99%